INNOVATIVE GOVERNANCE PENGELOLAAN SAMPAH MENJADI ENERGI LISTRIK PADA TPS 3R JAMBANGAN KOTA SURABAYA - Herlianto, Rizal Priatama; Megawati, Suci (Universitas Negeri Surabaya, 2024)
Innovative governance is a change in policy or management practice that results in improvement in the quality, quantity and level of services provided by an organisation. Innovation in waste management into electrical energy is a new breakthrough in reducing residual waste contained in TPS 3R Jambangan. Even in developed countries, it has been widely applied to reduce the volume of waste. However, it is different from the application found at TPS 3R Jambangan because it still has obstacles such as limited human resources, the community is not interested and the machine is damaged. The purpose of this research is to describe innovative governance of waste management into electrical energy at TPS 3R Jambangan. In describing innovative governance of waste management into electrical energy using the theory put forward by (Anttiroiko et al., 2011), namely democratic, managerial, development and service functions of government. This research method is descriptive qualitative. Where data is collected using observation, interview, and documentation techniques. The data that has been collected is then analyses by reducing data, presenting data, and drawing conclusions. The results of this study are in innovative governance of waste management into electrical energy at TPS 3R. The democratic and managerial indicators are quite good, although not optimal. Meanwhile, the development is going well, and the service functions of government are not so optimal.